HUBUNGAN PENGETAHUAN PEREMPUAN TENTANG PROMOSI KESEHATAN DENGAN PENCEGAHAN KANKER PAYUDARA DAN SERVIKS TAHUN 2020 - Ida Farida; Yati Afiyati; Andita Rahmadani (Nusantara Hasana Journal, 2021)
Knowledge is the result of "knowing" and this happens after people have sensed a certain object. Cervical cancer is a primary malignant tumor originating from the cervical canal or serving. While breast cancer is a disease that causes because of excessive growth or uncontrolled development of breast cells (tissue). Research Objectives To determine the relationship of women's knowledge about health promotion with the prevention of breast cancer and cervical cancer. The research method in this study uses Google Form. The population is women in Indonesia that got 100 respondents. Sampling technique by giving questionnaires to respondents using a web-based interactive service. This research uses Chi-Square Test, with the result of p-value 0,000 <0.05. Conclusion that there is a Relationship between Women's Knowledge about Health Promotion and the Prevention of Breast and Cervical Cancer in Indonesia.